2017
DOI: 10.1002/ecy.1816
|View full text |Cite
|
Sign up to set email alerts
|

Contribution by vertebrates to seed dispersal effectiveness in the Galápagos Islands: a community‐wide approach

Abstract: Seed dispersal and seedling recruitment are crucial phases in the life cycle of all spermatophyte plants. The net contribution of seed dispersers to plant establishment is known as seed dispersal effectiveness (SDE) and is defined as the product of a quantitative (number of seeds dispersed) and a qualitative (probability of recruitment) component. In Galápagos, we studied the direct contribution to SDE (number of seeds dispersed and effect on seedling emergence) provided by the five island groups of frugivores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 48 publications
2
32
0
1
Order By: Relevance
“…Second, by separating effects of deinhibition and scarification, we found that comprehensive experimental designs may not be important for capturing most of the other variations in gut passage effects. In this system, plant species varied substantially in the effect of gut passage on germination, but a great majority of the effect size was explained by pulp removal, with smaller and inconsistent effects of gut passage by the different frugivores, consistent with previous studies (Kelly et al., ; Nogales et al., ; Robertson et al., ). Researchers focused on dynamics at the community scale may more quickly and cost‐effectively describe plant species’ dependence on gut passage by conducting experiments using only whole fruits and manually depulped seeds, or with gut passage trials using a subset of frugivores.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Second, by separating effects of deinhibition and scarification, we found that comprehensive experimental designs may not be important for capturing most of the other variations in gut passage effects. In this system, plant species varied substantially in the effect of gut passage on germination, but a great majority of the effect size was explained by pulp removal, with smaller and inconsistent effects of gut passage by the different frugivores, consistent with previous studies (Kelly et al., ; Nogales et al., ; Robertson et al., ). Researchers focused on dynamics at the community scale may more quickly and cost‐effectively describe plant species’ dependence on gut passage by conducting experiments using only whole fruits and manually depulped seeds, or with gut passage trials using a subset of frugivores.…”
Section: Discussionsupporting
confidence: 88%
“…First, by assessing the sources of variation in gut passage effects, we show that lumping frugivores into functional groups appears appropriate when considering effects of gut passage on germination, as there were not large or consistent differences across disperser species in their effects on germination. So long as the distinction between seed dispersers and seed predators was in place (which in this case involved complete seed predation, which may often not be the case; Shiels, ), we would have reached appropriate inferences by grouping the dispersers in this system a priori as “passerines/fruit dove,” “small birds/large birds,” or more simply “birds.” The grouping of species into functional groups is already widely used in seed dispersal research, especially for considering differences in effectiveness of different groups of dispersers (González‐Castro et al., ; Nogales et al., ). Our results emphasize that functional groupings for gut passage effects should be based on digestive morphology and diet rather than loosely on phylogeny and body size, which would have grouped the Alopecoenas ground dove and Ptilinopus fruit dove in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on seed dispersal effectiveness has largely focused both on gut passage effects and on the spatial patterns of seed deposition generated by different disperser species, with consequences for recruitment (Jordano & Schupp, ; Schupp, ; Schupp et al., ). Gut passage effects on germination can vary among groups of seed dispersers (Nogales et al., ; Traveset, ), while the fates of seeds and seedlings often differ between microhabitats and habitat types due to spatial variation in biotic and abiotic factors, such as seed predator activity, irradiance, soil humidity or intra‐ and interspecific competition (Gómez‐Aparicio, ; González‐Varo, Nora, & Aparicio, ; Rey & Alcántara, ; Schupp, ). The latter explains why space has been a major factor when considering the quality of seed dispersal services provided by different animal partners (Calviño‐Cancela & Martín‐Herrero, ; Escribano‐Ávila et al., ; Rother et al., ; Schupp et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Gut passage effects on germination can vary among groups of seed dispersers (Nogales et al, 2017;Traveset, 1998), while the fates of seeds and seedlings often differ between microhabitats and habitat types due to spatial variation in biotic and abiotic factors, such as seed predator activity, irradiance, soil humidity or intra-and interspecific competition (Gómez-Aparicio, 2008;González-Varo, Nora, & Aparicio, 2012;Rey & Alcántara, 2014;Schupp, 1995). The latter explains why space has been a major factor when considering the quality of seed dispersal services provided by different animal partners (Calviño-Cancela & Martín-Herrero, 2009;Escribano-Ávila et al, 2014;Rother et al, 2016;Schupp et al, 2010).…”
mentioning
confidence: 99%